Transculturação narrativa: dos diálogos de Ángel Rama e Berta Ribeiro à edição de Antes o mundo não existia - Ananda Nehmy de Almeida (2022)
The objective of this thesis is to retake Transculturación narrativa en América Latina, by Ángel Rama (1982) and, from the perspective of the Uruguayan critic in relation to the passage from indigenous oral traditions to printed material, approach Antes o mundo não existia (1980), prefaced by Berta Ribeiro. The thesis focus is justified by the Uruguayan critic´s highlights in the text showing the contribution of the anthropologist. To the development of the thesis were used bibliographical and archival sources researched in Memorial Darcy Ribeiro where Berta and Darcy Ribeiro´s collections and libraries are located. Berta Ribeiro´s collection offers subsidies to elucidate the book´s edition process connected to Desana mythology, the participation of indigenous people and other aspects related to transculturation, to the archive and to the repertoire. So, this thesis is structured in four chapters, namely: “Contrapoints of transculturation”, “Transculturation, archive and repertoire”, “From correspondence to edition” and “Exhibition catalog and critical edition”. The first chapter reviews the critical reception of Rama´s book, mainly Barros Cunha´s (2005) studies, and the basic sources used by the Uruguayan critic as Contrapunteo cubano del tabaco y el azúcar by Fernando Ortiz, in addition to the anthropological essays by José María Arguedas. This thesis retakes the critical clash between Ángel Rama and Vargas Llosa about Los ríos profundos and the latin-american romance observing how ethnography and oral traditions reappear in the reading proposed by the Uruguayan critic. To re-discuss the narrative transculturation concept within the memory, in the second chapter, I relate it to the notions of archive and repertoire, according to Diana Taylor (2013) and to the conception of myth in Lévi-Strauss (2003). This review brings the study of the correspondence between Ángel Rama and Antonio Candido, organized by Pablo Rocca in 2018, and the one maintained by the Uruguayan critic with Darcy and Berta Ribeiro, published in 2015 and organized by Haydée Ribeiro Coelho and Pablo Rocca. The next chapters contextualize the publication and dissemination of the first edition of Antes o mundo não existia. Letters from Berta Ribeiro elucidate how the contact and narrative transculturation of oral and written cultures took place, in order to enable the ethnography and the first edition of Antes o mundo não existia. The correspondence between Berta Ribeiro and the Salesian Fathers Franz Knobloch and Casimiro Bėkšta is also analyzed. The study of the Berta Ribeiro´s correspondence with the French anthropologist Dominique Buchillet, who reviews the 2nd edition of Antes o mundo não existia, complements this set. Letters containing reports by the anthropologists refer to their field research and the organization of the exhibition “Os índios das águas pretas”. This thesis ends with the comparison between these editions of Antes o mundo não existia mediated by excerpts from the manuscript of the origin myth.